Infection Control - Basak, Silpi (IntechOpen, 2013)
Health Care associated infection (HAI) is an emerging problem worldwide. HAI causes increased morbidity, mortality and average length of stay of the patient in the hospital. HAI also imposes economic burden on the patient, health care set up and also State and National Health care system. It has been estimated that 5 10 % of all hospital admission suffers from HAI even in developed countries. But 30% of HAI are preventable, if we follow the infection control practices properly especially hand hygiene while giving patient care. Hence, in this book importance has been given to Infection Control practices along with emerging trends of HAI due to Pseudomonas aeruginosa, Acinetobacter species etc.